A prospective study of fetomaternal outcome in cases of placenta previa - Kadikar, Gunvant K.; Gandhi, Mayur R.; Kapadia, Rakesh R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The incidence of placenta previa ranges from 0.5-1% amongst hospital deliveries. Placenta previa is major cause of antepartum haemorrhage and is potentially devastating complication. Obstetric haemorrhage is most common cause for maternal and perinatal morbidity and mortality in India. This study aimed to determine frequency, type of placenta previa, risk factors and adverse fetomaternal outcomes of placenta previa. Methods: This was a prospective study carried out in Department of Obstetrics and Gynaecology, Government Medical College and Sir-T hospital, Bhavnagar from July 2007 to July 2009 to analyze fetomaternal outcome in cases of placenta previa. All patients of placenta previa with gestational age > 28 weeks up to full term were included in the study. All cases were confirmed by Ultrasound examination. All cases were carefully analyzed to find out the incidence, type of placenta previa, its clinical presentation and its outcome in relation to mode of delivery, birth weight, maternal and perinatal morbidity. Results: There was total 50 cases of placenta previa out of 5636 deliveries. The prevalence of placenta previa was 0.88% and was more commonly present among multiparous women (82%). Most common type was type IV placenta previa in 23 (46%) cases followed by type III in 11 (22%) cases. Out of 50 cases, 06 (12%) cases had atonic PPH and 02 (04%) cases underwent peripartum hysterectomy. Most common predisposing factors were age >35 years (04%), multiparity (50%), previous cesarean section (16%) and previous history of abortion (12%). All cases of perinatal mortality were between 28 to 30 weeks weighing between 1-1.5 kg. There was no maternal mortality in this study. Conclusions: Managing a case of placenta previa during pregnancy poses a great challenge to every obstetrician in present day obstetrics due to its increased risk of maternal and perinatal complications.